Assessing the Impact of Land Cover Change on Peak Discharge Using HEC-HMS: Case Study of the Batang Timpeh Watershed, Indonesia - Deddy Irwansyah; Indratmo Soekarno; I Nyoman Yogi Mertawiasa; Resi Nisa Nurhadid; Yosephina Puspa Setyoasri (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Recent deforestation driven by illegal logging, forest fires, and land conversion for oil palm plantations has significantly altered land cover conditions; however, its quantitative impact on peak discharge in the downstream Batang Timpeh Watershed remains poorly understood. This study aims to assess the impact of land cover change on peak discharge using the HEC-HMS model with the SCS-CN method, calibrated against the bankfull discharge of the Batang Timpeh River. Land cover data from 2015, 2019, and 2022 were analyzed using ArcGIS and integrated into hydrological simulations for a 20-year return period (Q20). The results indicate that peak discharge increased from 469.60 m³/s in 2015 to 478.30 m³/s in 2022, representing a 1.85% increase. This increase is associated with higher Curve Number (CN) values and the expansion of impervious areas, indicating reduced infiltration capacity and a more rapid runoff response. These findings demonstrate that land cover change has significantly contributed to the intensification of peak discharge and increased flood potential in the downstream area, providing a quantitative basis for improving land use planning and developing more effective flood risk mitigation strategies in the Batang Timpeh Watershed, particularly in Dharmasraya Regency.